Comparative economic analysis of land valuation and land market factors using the examples of Germany and France - Naárné Tóth, Zsuzsanna; Orlovits, Zsolt; Naár , Antal Tamás; Sőreg, Ádám Pál (Studia Mundi – Economica, 2016)
There is no uniformly applied land valuation methodology in the European Union. Methods differ according to the aims and techniques of the valuation. Hence the determination of the economic value and the price of agricultural land is problematic. In our research the land valuation systems of two EU Member States (Germany and France) were examined. In our opinion, some elements of the described methods may be useful in the modernization of the Hungarian system of land valuation. In addition to the land valuation systems, the economic factors influencing the market value of agricultural land, the existing market prices and their influencing factors in Germany and France were analyzed.